Unraveling the efficacy of nitrification inhibitors (DCD and DMPP) in reducing nitrogen gases emissions across agroecosystems: A three-decade global data synthesis (1993–2021). (15th September 2022) - Tufail, Muhammad Aammar; Naeem, Asif; Arif, Muhammad Saleem; Farooq, Taimoor Hassan; Shahzad, Sher Muhammad; Dar, Afzal Ahmed; Albasher, Gadah; Shakoor, Awais
Graphical abstract: Highlights: A global meta-analysis of nitrogen inhibitors to reduce N2 O emissions across agro-system. Overall, DCD and DMPP mitigated N2 O emissions by 47% and 39%, respectively. Relative efficacy of DCD was higher in chemically fertilized and acidic soils. DCD is the exclusive option for vegetable fields, while DMPP is more suitable for maize fields. Abstract: The production of biofuels from crop biomass is now seen as a practical renewable energy alternative, reducing overdependence on fossil fuels and limiting global warming from greenhouse gases. With respect to nitrogen emissions from biomass, it is claimed that nitrification inhibitors (NIs), particularly dicyandiamide (DCD) and 3, 4-dimethylpyrazole phosphate (DMPP), can reduce these nitrogen losses. Nevertheless, the effectiveness of these NIs to reduce N2 O emissions and NH3 volatilization under different environmental conditions remains largely unclear. To this aim, a global meta-analysis was performed using 366 observations from 149 peer-reviewed research studies to quantify the responses of N2 O emissions and NH3 volatilization to the application of DCD and DMPP under different conditions. Based on the meta-analysis, DCD and DMPP can significantly reduce N2 O emissions by 47% and 39%, respectively. The efficiency of DCD in reducing N2 O emissions was much higher (12%) than that of DMPP when used together with chemical fertilizers. Interestingly, DCD tended to be more effective (9–10%) in incubation and field trials, while DMPP showed 39% higher efficacy. Concerning NH3, fertilizer-type, and soil pH, specific effects of NIs were not significant overall. Although DCD (pot experiments) and DMPP (incubation experiments) showed 30% and 46% higher NH3 emissions, respectively, their effects were not significant under field conditions. According to meta-analysis, DCD and DMPP have demonstrated great potential to reduce N2 O emissions. Importantly, the efficacy of such eco-friendly interventions could further be improved if the preferences described above are followed. Therefore, it will take further investigation to understand the mechanisms underlying the relatively higher efficacy of one NI over the other under specific conditions, including crop type, the nature of experiment, and other edaphic factors.